Effect of Natural Disasters on Local Nonprofit Activity. (12th May 2014) - Pena, Anita A.; Zahran, Sammy; Underwood, Anthony; Weiler, Stephan
Abstract Disaster damage levels are matched to county‐level nonprofit activity indicators. Using dynamic panel‐data estimation, nonprofit net assets (and nonprofit revenue to a lesser extent) defined at this local level are found to be positively correlated with disaster event damage levels, consistent with a post‐disaster giving mechanism. Magnitudes are relatively small, suggesting a distributed downstream flow of benefits to local nonprofits from larger national organizations. Furthermore, disaster damage at a lag is associated with only minor increases in the count of local nonprofit organizations at the county level. The relative impacts of assets and nonprofit counts in particular indicate that existing nonprofits have the established credibility and networks to be reliable conduits for post‐disaster asset flows. If local nonprofits are an indicator of regional social capital, the findings suggest that disasters reveal the resilience of social capital structures in the face of crisis along the focal dimension of nonprofit activity.